Experimental Analysis on Active Bandwidth Estimation Tools for Mesh Wireless Local Area Network (WLAN) - Mashur, Samhuji (2013)
Available bandwidth estimation is useful for route selection in a network environment. While many tools has been created to estimate the available bandwidth, mainly by two techniques passive and active measurement. Passive measurement is performed by observing the traffic without intruding the network. Active measurement on the other hand, will probe the network by generating packet traffic into the network to perform the measurement with the availability of multiple available bandwidth estimation tools around, the question is which bandwidth estimation tool will be the best to perform the task in a given network situation? Which tools perform the best when fluctuation of bandwidth happens in a network? In this research, the aim is to test a number of bandwidth estimation tools in active method by simulating traffic in a real testbed setup in open wireless environment. The focus is wireless environment, therefore it will be varies in terms of number of hops and bandwidth between excess points. To further test the tools, simulation will also be done on an optimum network and network with external traffic where other packet traffic happens to be around while the experiment is running. Expected result is dependable on the consistency result of each tool when tested with different wireless environment. Further recommendation will be given on which tool is suitable to use base on the testing result.